The Effect Of Retrenchment Policy On Financial Recovery Of Hospitality, Restaurant and Tourism Sub-Sector Companies During The Covid-19 Pandemic - Ribka Tasya; Liza Alvia (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
The purpose of this study is to investigate how retrenchment practices affected the company's ability to recover financially from the Covid-19 pandemic in the years 2020–2022. The population in this study were all (41) hotel, restaurant and tourism sub-sector companies listed on the Indonesia Stock Exchange with a research sample of 27 companies. Logistic regression analysis was employed as the data analysis technique in this study. The return on assets change index is used to quantify the financial recovery. The assets retrenchment variable is measured using the assets retrenchment ratio formula and the expenses retrenchment variable is measured using the expenses retrenchment ratio formula. Meanwhile, the downscoping variable is measured using the Herfindahl index. The results of this study indicate that assets retrenchment and expenses retrenchment have no effect on financial recovery. Meanwhile, downscoping has an effect on financial recovery.